Specificity of Internal Dialogue Means in A.P. Chekhov’s Prose of 1888-1894 - Olga Aleksandrovna Prokhvatilova; Nadezhda Eduardovna Fotina (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2016)
The paper presents the study results of one of the dialogue types typical of author's narrative in A.P. Chekhov's stories written in 1888-1894 – the indirect self-speech. It is stated that the indirect self-speech is a major means of creating internal dialogue. The article offer a set of various language signs that point to the indirect self-speech realization. Grammatical means include constructions with different verbal forms, expressive syntax, means of changing modal and temporal aspects, and indefinite pronouns, adverbs, demonstrative and intensifying particles. Lexical signals of the indirect self-speech are being represented both graphically and with citations that are not marked graphically by the author. It is revealed that the citations prevail in the texts under study and are characterized by stylistically marked words and phrases, by vocabulary with expressively marked emotions. The essential predominance of grammatical means over lexical ones is discovered and attested to the specificity of the writer's style and the need to achieve the effect of objectiveness in narration. The main functions of the indirect self-speech in A.P. Chekhov's works of 1888-1894 are set out, a general function of switching the narration into a personal speech of a personage and some secondary ones that include logical evaluation as well as presenting emotional reaction of a personage.